EVALUASI PROGRAM SEKOLAH PENGGERAK DENGAN MODEL CIPP DI SDN 17 LAING KOTA SOLOK - Dona Nengsih; Abhanda Amra; Demina; Sirajul Munir; Jamilus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the context, input, process, and product of the evaluation of the driving school program at SDN 17 Laing, Solok City. This study uses a qualitative approach. This type of research is included in descriptive qualitative research that discusses the Evaluation of the Driving School Program Using the CIPP Model at SDN 17 Laing. Primary data sources are the supervisor, principal, 5 teachers, 2 students, and the committee chairman, and secondary data sources are school programs, teaching modules, data, documentation, and literature reviews. Data collection techniques use interviews and documentation. Data analysis techniques use data collection, data selection, data presentation, and data conclusions. The results of the study indicate that the evaluation of the driving school program at SDN 17 Laing, Solok City using the CIPP model is generally in accordance with the existing criteria. Context evaluation includes the suitability of the driving school program objectives with the school's objectives, the relevance of the driving school's objectives to the needs of teachers, students, and the community in accordance with the criteria. Input evaluation shows the potential and human resources, the availability of funding sources, physical infrastructure according to the criteria, and the need for improvements in IT facilities. Evaluation of the implementation process of consultative and asymmetric mentoring, implementation of human resource strengthening, implementation of new paradigm learning in the form of differentiated learning, P5 and extracurricular activities, data-based planning and digitalization of administration has met the criteria. Improvements are needed in improving the quality of human resources. Product evaluation includes an increase in the results of the 2024 educational report card in literacy and numeracy, the existence of differentiated learning teaching modules, P5 teaching modules, differentiated learning videos, P5 videos and changes in good habits of teachers and students in the learning process in the use of applications in learning, diverse media always sharing good practices in complexes and the independent teaching platform.